Clinical study of 99mTc-Rituximab combined with dyes double tracing for axillary sentinel lymph node biopsy after neoadjuvant chemotherapy for breast cancer - Zhuang, Minxue; Lin, Yidan; Qiu, HongBin; Chen, Wei; Wang, Ruo; Zeng, HuanHong; Lin, Mengbo; Zhang, Hui (Frontiers in Oncology, 2025)
Background and objectiveWhether sentinel lymph node biopsy (SLNB) after neoadjuvant chemotherapy (NAC) for breast cancer is an alternative to axillary lymph node dissection (ALND) remains controversial. In this study, the results of SLNB performed with 99mTc-Rituximab combined with dyes were analyzed, and the application value of the double-tracing method of 99mTc-Rituximab combined with dyes in SLNB after breast cancer NAC was evaluated, the feasibility of SLNB after NAC and the clinical application of the novel tracer 99mTc-Rituximab and its value in internal mammary lymph node(IMLN) was discussed.MethodsA retrospective analysis of 106 breast cancer patients who underwent post-NAC SLNB from August 2019 to August 2023 at Fujian Provincial Hospital, where SLNB was performed using 99mTc-Rituximab combined with dye imaging or dye imaging alone. The detection rate, sensitivity, false-negative rate, accuracy and the detection rate of internal mammary lymph node(IMLN) biopsy were compared between the two tracing methods.Results70 cases were included in the dual-tracer group, with a detection rate of 97.14% (68/70), an average number of detected SLNs of (6.06 ± 5.29), a sensitivity of 92.86% (26/28), a false negative rate of 7.14% (2/28), and an accuracy of 97.14% (68/70). 36 cases were included in the single-tracer group, with a detection rate of 66.67% (24/36), an average number of detected SLNs of (3.17 ± 3.073), a sensitivity of 54.55% (11/22), a false negative rate of 45.45% (10/22), and an accuracy of 72.22% (26/36). There were significant differences in the detection rate and the average number of detected SLNs between the two groups (detection rate: P=0.004; detection number: P=0.038), but there were no significant differences in the sensitivity, accuracy, and false negative rate (P>0.05). A total of 70 patients were examined for internal mammary lymph node biopsy with dual tracer, and 22 patients were detected with an imaging rate of 31.42% (22/70), and a detection rate of 72.72% (16/22).ConclusionsFor patients with breast cancer, the dual-tracer method combining radionuclide and dye for SNLB after neoadjuvant chemotherapy can improve the detection rate of sentinel lymph nodes and reduce the false-negative rate. In the long term, the quality of life of patients can be helped to improve by this approach. Compared with other tracers, 99mTc-Rituximab can improve the detection rate of internal mammary lymph nodes, with the characteristics of rapid clearance of injection site, less secondary lymph node visualization, and hypoallergenicity, which can be used as an ideal tracer for further research.